Compendium Quality of in-company vocational education and training - Gaylor, Claudia [Verfasser]; Follner, Magdalene [Verfasser]; Barkholz, Sylvia [Verfasser]; Düz, Fidan [Verfasser]; Kohl, Matthias [Verfasser]; Fischer, Martin [Verfasser]; Kretschmer, Susanne [Verfasser]; Reglin, Thomas [Verfasser]; Schemme, Dorothea [Mitarbeiter] (Bundesinstitut für Berufsbildung, 2015)
"The present compendium is the result of the pilot project programme for 'Quality development and quality assurance in in-company initial vocational education and training'. This programme was carried out nationwide from 2010 to 2013 under the oversight of the Federal Institute for Vocational Education and Training (BIBB) with funds from the Federal Ministry of Education and Research (BMBF) with ten pilot projects in the fields of crafts, industry and services. In conjunction with training practice in small and medium-sized enterprises, pathways to improvement of the quality of dual vocational education and training were designed and analysed. The compendium is intended primarily for people in charge of training in companies and for trainees. Educational staff at schools, inter-company educational establishments and institutions in the field of vocational training can also benefit from the approaches to improving quality provided by the compendium." (Excerpt, BIBB-Doku)
Quality of in-company vocational education and training
Dt. Ausg. u.d.T.: Leitfaden Qualität der betrieblichen Berufsausbildung
Keywords: S 1.3 Berufliche Erstausbildung; L 6 Qualität; Betriebliche Berufsausbildung; Ausbildungsqualität; Rechtsgrundlage; Ausbilderqualifizierung; Ratgeber